2019
DOI: 10.31899/rh6.1021
|View full text |Cite
|
Sign up to set email alerts
|

Health financing and family planning in the context of Universal Health Care: Connecting the discourse

Abstract: Section one outlines salient features of health financing and UHC as well as related trends • Section two outlines health financing for FP, current emphasis of financing efforts and the evidence base• Section three outlines strategic purchasing and FP and its relationship with quality FP services • Section four proposes an organizing framework for strategic purchasing for FP, outlining purchasing elements and FP considerations MARCH 2019The Population Council conducts research and delivers solutions that impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Service exemption schemes for MCH, such as those in Sahelian countries, may also fail to include family planning as part of a continuum of care. 10 , 18 Even when family planning is included in a benefits package or service exemption scheme, this may not translate to provision. A seven-country study of health insurance schemes 19 concluded that despite the formal inclusion of family planning services in the national benefits packages examined, actual integration of these services faced challenges, with implications for the availability of family planning services in practice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Service exemption schemes for MCH, such as those in Sahelian countries, may also fail to include family planning as part of a continuum of care. 10 , 18 Even when family planning is included in a benefits package or service exemption scheme, this may not translate to provision. A seven-country study of health insurance schemes 19 concluded that despite the formal inclusion of family planning services in the national benefits packages examined, actual integration of these services faced challenges, with implications for the availability of family planning services in practice.…”
Section: Resultsmentioning
confidence: 99%
“…Polity: why purchase The framework was originally developed with a specific emphasis on the quality provision of family planning. 9,10 In this paper, we have extended it to cover other SRH services. Following the framework (Table 1), we describe how the different elements of purchasing may influence quality of SRH care.…”
Section: Findings 5ps Frameworkmentioning
confidence: 99%
“…The WHO report has shown that accelerating UHC cannot be achieved without increasing financial protection and without inclusion of essential health services, which is also applicable to universal SRHR services ( 37 ). In many low-income countries, including Ethiopia, however, financing the SRHR services and others is still a major challenge for achieving universal SRHR services within the scheme of UHC, partly attributed to financial constraint.…”
Section: Srhr Services Included In the Current Ethiopian Financing An...mentioning
confidence: 99%
“…On family planning, Marshall 33 postulates that in some countries, religion plays a factor in government's choices of implementing certain family planning policies and reforms above others. Family planning may also be more frequently excluded given the high levels of donor dependency (especially for financing commodities) 34 and low cofinancing requirements. 35 36 Finally, information required to prioritising a wide range of interventions may not have been as widely available for older HBPs.…”
Section: 6mentioning
confidence: 99%